Laporan "Regional Seminar on Tropical Urban Ecosystems Studies" - Regional Workshop on Tropical Urban Ecosystems Studies (1988 : Bangi); Tajuddin Kechik (Skudai : Universiti Teknologi Malaysia, 1988)
42